2013
DOI: 10.1200/jco.2013.31.15_suppl.3016
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor PD-L1 expression and immune biomarkers with clinical activity in patients (pts) with advanced solid tumors treated with nivolumab (anti-PD-1; BMS-936558; ONO-4538).

Abstract: 3016 Background: The immune checkpoint receptor programmed death-1 (PD-1) negatively regulates T-cell activation. In a phase I study, nivolumab, a PD-1 receptor blocking antibody, demonstrated durable clinical activity. Evaluation of the expression of the PD-1 ligand, PD-L1, by IHC with the 5H1 Ab suggested a correlation between pretreatment tumor PD-L1 expression and clinical response (Topalian et al, NEJM 2012). Methods: 304 pts with non-small cell lung cancer (NSCLC, n=127), melanoma (MEL, n=107), renal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 0 publications
2
66
0
1
Order By: Relevance
“…In the present study, we report absolute percentages of PD-L1 positivity without applying pre-set cut-offs as suggested by several large studies. [34][35][36][37][38] In addition, we used the PD-L1 antibody clone SP263 for immunohistochemistry, which has been recommended as companion diagnostic in previous studies targeting PD-1/PD-L1 axis. 7,39,40 To avoid possible confounding effects of preoperative treatment on tumor immunology and TME, we included exclusively primary resected, therapy-na€ ıve hSTS in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we report absolute percentages of PD-L1 positivity without applying pre-set cut-offs as suggested by several large studies. [34][35][36][37][38] In addition, we used the PD-L1 antibody clone SP263 for immunohistochemistry, which has been recommended as companion diagnostic in previous studies targeting PD-1/PD-L1 axis. 7,39,40 To avoid possible confounding effects of preoperative treatment on tumor immunology and TME, we included exclusively primary resected, therapy-na€ ıve hSTS in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The antagonist may not be strong enough as an alternative to immune checkpoint antibody. Lastly, it showed in recent clinical research that the objective response rate of anti‐PD‐1 or anti‐PD‐L1 therapy was below expectation in some patients, which may be attributed to that the immune response in tumor microenvironment is really complex and dynamic . Altogether, the nanovaccine may need to develop further combination with other therapeutic modality in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the relationship between PD‐L1 expression and nivolumab efficacy, many studies have reported relationships between treatment benefit with nivolumab and PD‐L1 expression levels 16,19,20 . One study, using a 5% expression threshold, showed the potential of pretreatment PD‐L1 tumor expression as a predictive marker to indicate which patients would benefit from treatment 19 .…”
Section: Discussionmentioning
confidence: 99%